PERSEPSI NELAYAN TERHADAP PRAKTIK DESTRUKTIVE FISHING DI WILAYAH PESISIR SAPE: ANALISIS TEMATIK MANUAL ALA NVIVO: Fishermen’s Perception Of Destructive Fishing Practices In The Sape Coastal Area: A Manual Thematic Analysis By Nvivo - Marini, Ida Ayu Ketut; Sativa, Denianto Yoga (Ganec Swara, 2025)
This study aims to explore fishermen’s perceptions of destructive fishing practices in the coastal area of ​​Sape, Bima Regency. The method used was a descriptive approach using a five-point Likert scale questionnaire. Data were analyzed using a manual thematic technique based on NVivo principles, which grouped statements into five categories: ecological impacts, socio-economic impacts, legal knowledge, attitudes toward the environment, and perceptions of the government’s role. The analysis results indicate that fishermen have a high awareness of the ecological and socio-economic impacts of destructive fishing. They also demonstrated a positive attitude toward environmental conservation and law enforcement, although perceptions of government assertiveness remained low. These findings provide important insights for formulating policies for community-based fisheries resource management